Private equity investment committee paper on Sogrape, SGPS, S.A - Duarte, Afonso Maria Jardim Gonçalves Teixeira (2020)
This work project aims to study a private equity deal using a Leverage Buyout Model of the Portuguese private equity Sogrape, operating in the wine sector. In this specific part is define how much is Sogrape worth and how will be their initial capital structure. The starting point was the market and company analysis where it was concluded it is needed to take advantage of Sogrape’s positioning as a leader in the Portuguese market, promoting consolidation through an acquisition and empower the company positioning as a distributor. Regarding the international markets, part of the strategy involves to change the route-to-market in USA, a key market to this sector. In the other market clusters as growth platforms and mature markets, the plan involves the promotion of sales through an increase in marketing expenses as well as focusing on the segments that is expected to face a higher growth rate in the following years and where Sogrape holds more competitive advantages such as light wines. After this analysis, a valuation of Sogrape and Esporão was needed. Knowing the drawbacks of a Discounted Cash Flow valuation a valuation based on multiple was realized. To have the most complete multiple analysis we not only consider Sogrape most comparable companies multiples but also how much the market is currently paying looking for the last transactions multiples. Reaching a value for Sogrape value it was then possible to calculate how much equity and debt would be needed to buy Sogrape bearing in mind all the debt covenants (Leverage Amount, Interest and Cash Cover ratios) and expected cash generation.Keywords (up to four): Private Equity, Valuation, Multiples